Mitochondrial Degeneration and Autophagy Associated With Delayed Effects of Radiation in the Mouse Brain - Sharma, Neel K.; Stone, Sasha; Kumar, Vidya P.; Biswas, Shukla; Aghdam, Saeed Y.; Holmes-Hampton, Gregory P.; Fam, Christine M.; Cox, George N.; Ghosh, Sanchita P. (Frontiers in Aging Neuroscience, 2019)
Mitochondria are associated with various radiation responses, including mitophagy, adaptive responses, genomic instability, the bystander effect, and apoptosis. Mitochondria play a key role in maintaining cellular homeostasis during stress responses, and mitochondrial dysfunction contributes to aging, carcinogenesis and neurologic diseases. In this study we have investigated the mitochondrial degeneration and autophagy in the hippocampal region of brains from mice administered with BBT-059, a long-acting interleukin-11 analog, or its formulation buffer 24h prior to irradiation at different radiation doses collected at six and twelve months post irradiation. The results demonstrated a higher number of degenerating mitochondria in 12Gy BBT-059 treated mice after six months and 11.5Gy, BBT-059 treated mice after twelve months as compared to the age matched naïve (non-irradiated control animals). Apg5l, Lc3b and Sqstm1 markers were used to analyze the autophagy in brain, however only Sqstm1 marker exhibited significantly reduced expression after twelve months in 11.5Gy, BBT-059 treated mice as compared to naïve. In conclusion, our results demonstrated that higher doses of ionizing radiation can cause persistent upregulation of mitochondrial degeneration. Reduced levels of Sqstm1 can lead to an impaired removal of damaged mitochondria that can result in increased mitochondrial mass and may lead to neurodegenerative diseases.